2013
DOI: 10.1371/journal.pone.0053089
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Global Increases in Water Use Efficiency: Why Have We Overestimated Responses to Rising Atmospheric CO2 in Natural Forest Ecosystems?

Abstract: BackgroundThe analysis of tree-ring carbon isotope composition (δ13C) has been widely used to estimate spatio-temporal variations in intrinsic water use efficiency (iWUE) of tree species. Numerous studies have reported widespread increases in iWUE coinciding with rising atmospheric CO2 over the past century. While this could represent a coherent global response, the fact that increases of similar magnitude were observed across biomes with no apparent effect on tree growth raises the question of whether iWUE ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 23 publications
3
62
1
Order By: Relevance
“…Net photosynthetic carbon assimilation (A net ), stomatal conductance (g s ), and evapotranspiration (E) were subsequently measured at growth light intensity (1400 mmol quanta m 22 s 21 ) once steady-state assimilation was achieved. IWUE was calculated as A/g s , according to Silva and Horwath (2013). A/C i curves were measured on days 0 and 36.…”
Section: Photosynthetic Gas Exchangementioning
confidence: 99%
“…Net photosynthetic carbon assimilation (A net ), stomatal conductance (g s ), and evapotranspiration (E) were subsequently measured at growth light intensity (1400 mmol quanta m 22 s 21 ) once steady-state assimilation was achieved. IWUE was calculated as A/g s , according to Silva and Horwath (2013). A/C i curves were measured on days 0 and 36.…”
Section: Photosynthetic Gas Exchangementioning
confidence: 99%
“…For example, tree ring widths potentially record changes in tree productivity, but low-frequency growth trends attributable to rising CO 2 concentrations might be removed by standardization (Melvin and Briffa, 2008;Cecile et al, 2013), in which case the inversion algorithm (like any other reconstruction method) would converge towards unrealistic trends that are exempt of any CO 2 imprint. Similarly, it has been argued by Silva and Horwath (2013) that, due to an artifact of calculation, δ 13 C chronologies might systematically overestimate the response of carbon isotopes to rising CO 2 concentrations, therefore creating artificial increases in reconstructed water use efficiency. However, as mentioned by McCarroll and Loader (2004) and also by Silva and Horwath (2013) for the particular case of CO 2 effects, the solution might lie in the use of multiple proxies, as it is proposed here.…”
Section: Is the Reconstruction Affected By Changes In Atmospheric Co mentioning
confidence: 99%
“…The results of Berninger et al (2004) show that, although photosynthesis increases in response to increasing CO 2 concentrations, tree growth rate cannot parallel the increase in photosynthesis because the potential growth rate is limited directly by temperature through nitrogen mineralization. The apparent fertilization effect of the models, related to water use efficiency (WUE) enhancement, itself due to a decrease in stomatal area, has not been observed in experimental chambers or in tree-ring series (Gedalof and Berg, 2010;Silva and Horwath, 2013). There is therefore much controversy as to whether the increase in CO 2 since the beginning of the industrial period has enhanced growth, with much recent evidence reporting changes in plant physiological processes but not in growth (Huang et al, 2007;Andreu-Hayles et al, 2011;Peñuelas et al, 2011;Girardin et al, 2012;Lévesque et al, 2014).…”
Section: Tree-growth Process Modelsmentioning
confidence: 99%
“…Without the fertilization effect, tree growth will decrease because of lack of water (the precipitation deficit is amplified by more evapotranspiration), but if the latter effect is included, tree-growth will increase. As mentioned in the literature review in the introduction section, this fertilization effect is not always observed on living trees and is subject to controversy (Gedalof and Berg, 2010;Silva and Horwath, 2013).…”
Section: Calibration and Predictionmentioning
confidence: 99%